Length–Weight Relationship of Skipjack Tuna (Katsuwonus pelamis) Landed at Tulehu Village, Maluku - Rocky Udimera; Domey Lowits Moniharapon; Imanuel V.T. Soukotta; Rahman Rahman; Junita Supusepa (Nekton, 2025)
Skipjack tuna (Katsuwonus pelamis) caught in the Banda Sea using purse seines and pole-and-line (huhate) fishing gear has shown a decrease in population size parameters. The parameters observed included size distribution and length–weight relationships, both of which serve as indicators of the size at first capture and first gonadal maturity. This study aimed to analyze the growth pattern of skipjack tuna landed by fishermen at Tulehu fishing port from April to June 2025. The analysis covered fish size distribution and the length–weight relationship. The results showed that the total length distribution of skipjack tuna caught in Tulehu waters reached its highest average in June (24 cm). The highest standard deviation of total length was observed in April (21.7 cm), while the lowest occurred in May (13.4 cm), suggesting that the skipjack population in Tulehu waters represents different recruitment groups. The length–weight relationship obtained was expressed as W = 0.000008 L³·⁰¹⁴⁷, indicating positive allometric growth, meaning that weight increases faster than length. The highest mean weight was recorded in June, with the greatest standard deviation observed in April. Based on these findings, it is recommended that the current size and weight data be used to determine the optimal capture size for skipjack tuna. Furthermore, fish at this stage are in the process of gaining additional body mass, which serves as an energy reserve for spawning activities.